2007
DOI: 10.1677/jme-06-0014
|View full text |Cite
|
Sign up to set email alerts
|

Role of stromal cell-derived factor 1 (SDF1/CXCL12) in regulating anterior pituitary function

Abstract: Chemokines are key factors involved in the regulation of immune response, through the activation and control of leukocyte traffic, lymphopoiesis and immune surveillance. However, a large number of chemokines and their receptors are expressed in central nervous system (CNS) cells, either constitutively or induced by inflammatory stimuli, playing a role in many neuropathological processes. Stromal cell-derived factor 1 (SDF1) is a chemokine whose extra-immunological localization and functions have been extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 46 publications
2
38
0
1
Order By: Relevance
“…We previously showed an autocrine/ paracrine mitogenic activity of SDF1 in cell lines and primary cultures of human glioblastoma multiforme coexpressing CXCR4 (16,18). In the present study, most of pituitary adenomas showed a similar pattern of coexpression, suggesting In addition, the high percentage of human pituitary adenomas expressing CXCR4 suggests that alterations of CXCR4 activity, possibly via a deregulated SDF1 secretion from the adenomatous cells themselves, the hypothalamus, or directly coming from the bloodstream (26), may contribute to the clonal expansion of transformed pituitary cells.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We previously showed an autocrine/ paracrine mitogenic activity of SDF1 in cell lines and primary cultures of human glioblastoma multiforme coexpressing CXCR4 (16,18). In the present study, most of pituitary adenomas showed a similar pattern of coexpression, suggesting In addition, the high percentage of human pituitary adenomas expressing CXCR4 suggests that alterations of CXCR4 activity, possibly via a deregulated SDF1 secretion from the adenomatous cells themselves, the hypothalamus, or directly coming from the bloodstream (26), may contribute to the clonal expansion of transformed pituitary cells.…”
Section: Discussionsupporting
confidence: 66%
“…More recently, chemokines acquired a relevant role in the physiology, pathology, and tumor transformation of different cell types, although, to date, few studies addressed their role in the regulation of normal and tumor pituitary cell functions (26). For example prosecretory effects of GRO (member of the IL-8 family) in rat anterior pituitary cells were reported (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside the hematopoietic system, SDF-1 is essential for cardiogenesis, vascularization of the gastrointestinal tract, limb myogenesis, and morphogenesis of the central and peripheral nervous systems (CNS and PNS) (Ma et al, 1998;Zou et al, 1998;Tachibana et al, 1998;Li and Ransohoff, 2008;Ödemis et al, 2005). In the adult nervous system, expression of SDF-1 and its receptor, CXCR4, persists in astrocytes, microglial cells, Schwann cells, distinct neuronal populations and endothelial cells (Li and Ransohoff, 2008), modulating neurotransmitter release from neurons and glia as well as hormone secretion from neuroendocrine cells (Bezzi et al, 2001;Barbieri et al, 2007;Lazarini et al, 2003;Rostène et al, 2007). SDF-1 and CXCR4 are additionally involved in several brain pathologies, such as acute ischemic and traumatic brain injuries, chronic brain infections and autoimmune diseases (Cartier et al, 2005;Li and Ransohoff, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…SDF-1␣ plays a critical role in cell migration because it is a chemotactic factor for T cells, monocytes, pre-B cells, dendritic cells, and hematopoietic progenitor cells (Barbieri et al, 2007). Gene inactivation of SDF-1␣ or of its receptor CXCR4 in mice impairs myelo-and lymphopoiesis Odemis et al, 2005).…”
mentioning
confidence: 99%